Prevalence of Osteoporosis among Middle Aged Women in Chitwan District of Nepal - Aryal, Dr. Bijay (International Journal of Pharmaceutical & Biological Archive, 2012)
Prevalence of Osteoporosis among Middle Aged Women in Chitwan District of Nepal